The role of CsrA in controls the extracellular electron transfer and biofilm production in Geobacter sulfurreducens - Hernández-Eligio, Alberto; Vega-Alvarado, Leticia; Liu, Xinying; Cholula-Calixto, Jessica; Huerta-Miranda, Guillermo; Juárez, Katy (Frontiers in Microbiology, 2025)
CsrA is a post-transcriptional regulator that controls biofilm formation, virulence, carbon metabolism, and motility, among other phenotypes in bacteria. CsrA has been extensively studied in γ-proteobacteria and firmicutes, However the cellular processes controlled for regulation in δ-proteobacteria remain unknown. In this work, we constructed and characterized the ΔcsrA mutant strain in Geobacter sulfurreducens to determine the involvement of the CsrA protein in the regulation of biofilm and extracellular electron transfer. The ΔcsrA mutant strain shows higher rates of insoluble Fe(III) reduction than the wild type using acetate as electron donor and the growth with fumarate and soluble (Fe(III)) was similar to wild type. Biofilm quantification and characterization by confocal laser scanning microscopy, showed that the ΔcsrA mutant produces up to twice as much biofilm as the wild type strain and more than 95% viable cells. Transcriptome analysis by RNA-seq showed that in ΔcsrA biofilms developed on an inert support, differentially expressed 244 genes (103 upregulated and 141 downregulated), including those related to extracellular electron transfer, exopolysaccharide synthesis, c-di-GMP synthesis and degradation. To validate the transcriptome data, RT-qPCR confirmed the differential expression of several selected genes in the ΔcsrA strain. Also, current production in microbial fuel cells was performed and the ΔcsrA strain produced 45–50% more current than the wild type. To identify the genes that changed expression in the ΔcsrA strain in the graphite electrodes in an MFC, a transcriptome analysis was performed 181 genes changed their expression in the ΔcsrA biofilms, of which 113 genes were differentially expressed only in MFC and 68 genes changed their expression as well as the transcriptome of biofilms grown on glass. In silico analysis of the 5′-UTR regions revealed that 76 genes that changed expression in the RNA-seq analysis have a consensus sequence for CsrA binding. To our knowledge this is the first report describing the involvement of CsrA in the regulation of extracellular electron transfer and biofilm in a member of the δ-proteobacteria.